Integration of Local Ecological Knowledge in Bird-of-Paradise Conservation Strategy: A Case Study in the Tabi and Saireri Traditional Areas - Edoward Krisson Raunsay (Universitas Pendidikan Mandalika, 2026)
This study examines the integration of local ecological knowledge into bird-of-paradise conservation strategies in the Tabi and Saireri customary areas, Papua, with a field focus in the East Sentani (Tabi) and South Yapen (Saireri) districts. Using qualitative methods with an ethnographic approach and case studies, this study aims to understand how indigenous communities manage and conserve birds-of-paradise through local wisdom practices embedded in their socio-cultural systems. Data were collected through in-depth interviews, participant observation, and focus group discussions with 32 participants consisting of traditional elders, traditional hunters, female forest managers, and village officials involved in customary-based conservation practices. Data analysis was conducted thematically to identify local values, rules, and institutional mechanisms that support conservation. The results revealed four main themes: (1) the establishment of taboo zones and sacred forests as habitat protection spaces, (2) seasonal hunting regulations and fishing gear restrictions, (3) ritual governance and customary sanctions to maintain ecological balance, and (4) community oversight mechanisms through customary institutions. The findings indicate that the integration of local knowledge is effective when recognized in formal policies through co-management schemes, strengthening the role of customary institutions, and recognizing customary sanctions in regional conservation regulations. Local knowledge-based strategies not only maintain the habitat and population of birds of paradise but also strengthen the social legitimacy of conservation policies. This study recommends the development of co-management instruments between local governments and indigenous communities as a contextual, inclusive, and sustainable policy framework for bird-of-paradise conservation in the Tabi and Saireri customary territories.